Pengaruh Lingkungan Kerja, Pelatihan, dan Insentif terhadap Kinerja Karyawan Pada PT. Erela Semarang - Aditya Dwi Christanto; Haryani Haryani (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study aims to analyze the influence of the work environment, training, and incentives on employee performance at PT. Erela Semarang. The research population includes 877 production employees working at the company. A random sampling technique was applied to ensure representative data, resulting in a sample of 100 production employees. The study adopts a quantitative approach, with data analyzed using multiple linear regression to examine the relationship between the independent variables and employee performance as the dependent variable. The findings reveal that the work environment has a positive and significant effect on employee performance, indicating that comfortable and supportive workplace conditions can improve productivity and job outcomes. In addition, training is proven to have a positive impact on employee performance, showing that skill development and knowledge improvement contribute to better work effectiveness. Furthermore, incentives also demonstrate a positive influence on employee performance, suggesting that financial or non-financial rewards can motivate employees to achieve higher performance levels and support organizational goals.